Biosorption of Chromium from Textile Wastewater Using Mimosa pudica Tannin Gel - Ramadhan, Yanuar Bekti; Sabrina, Aida Nur; Kwartiningsih, Endang (Equilibrium Journal of Chemical Engineering, 2021)
Abstract. The heavy metal content is very dangerous because it can pollute the environment. One of the heavy metals waste commonly found in the textile industry is chromium (Cr). Mimosa pudica is a weed plant and its availability is very abundant. However, it also contains tannin which can be developed into tannin gel biosorbent to adsorption heavy metal content in the wastewater. The purpose of this research is to study Mimosa pudica tannin as a Cr biosorbent from textile wastewater. There are two steps to synthesis tannin gel biosorbent. They are the tannin extraction and the condensation polymerization process. Tannin is easily soluble in water so the condensation polymerization process is needed to make it insoluble in water. The extraction of Mimosa pudica tannin was done using water solvent. The condensation polymerization process was done by the reaction of tannin extract and formaldehyde. The Cr content of textile industry wastewater in the Pasar Kliwon, Surakarta was 4 ppm. The results of the biosorption of Cr heavy metal using Mimosa pudica tannin gel showed that the remaining Cr heavy metal was 0.7098 ppm. It was already below the threshold which was 1 ppm. Keywords: biosorption, condensation polymerization, extraction, Mimosa pudica, tannin gel